Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]f(x)=2x-6\\
y=2x-6\\
2x=y+6\\
x=\frac{1}{2}y+3\\
f^{-1}(x)=\frac{1}{2}x+3\\
f^{-1}(2)=\frac{1}{2}\cdot2+3\\
f^{-1}(2)=1+3\\
f^{-1}(2)=4
[/tex]
a) Calculating f⁻¹(x)
[tex]y=2x-6\\ \\ x=2y-6\\ \\ 2y=x+6\\ \\ y=\frac{x+6}{2}\\ \\ \boxed{f^{-1}(x)=\frac{x+6}{2}}[/tex]
b) Calculating f⁻¹(2)
[tex]\boxed{\boxed{f^{-1}(2)=\frac{2+6}{2}=\frac{8}{2}=4}}[/tex]
[tex]y=2x-6\\ \\ x=2y-6\\ \\ 2y=x+6\\ \\ y=\frac{x+6}{2}\\ \\ \boxed{f^{-1}(x)=\frac{x+6}{2}}[/tex]
b) Calculating f⁻¹(2)
[tex]\boxed{\boxed{f^{-1}(2)=\frac{2+6}{2}=\frac{8}{2}=4}}[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.